2016
DOI: 10.1200/jco.2016.34.4_suppl.762
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of CEA and LDH in relation to KRAS status in patients with unresectable colorectal liver metastases.

Abstract: Background-While the significance of CEA, LDH and KRAS status as individual prognostic factors for patients with metastatic colorectal cancer has been addressed, the relationship and interdependence between these prognostic factors on survival is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…The current results are found significant height in serum levels of LDH and ALP in patients with CRC when compared to controls, which is in accordance with the observations of the previous researchers (Ojo et al, 2016;Saif et al, 2005;Connell et al, 2017). Ojo and colleagues showed significantly increasing values of serum LDH and ALP enzymes in CRC compared to controls, and reported that the associations between high activities of these enzymes and risk of developing cancer could be used as tumor markers in the prognosis, diagnosis and management of cancer (Ojo et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current results are found significant height in serum levels of LDH and ALP in patients with CRC when compared to controls, which is in accordance with the observations of the previous researchers (Ojo et al, 2016;Saif et al, 2005;Connell et al, 2017). Ojo and colleagues showed significantly increasing values of serum LDH and ALP enzymes in CRC compared to controls, and reported that the associations between high activities of these enzymes and risk of developing cancer could be used as tumor markers in the prognosis, diagnosis and management of cancer (Ojo et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Ojo and colleagues showed significantly increasing values of serum LDH and ALP enzymes in CRC compared to controls, and reported that the associations between high activities of these enzymes and risk of developing cancer could be used as tumor markers in the prognosis, diagnosis and management of cancer (Ojo et al, 2016). Consistently, Connell and workers showed that elevated serum levels of LDH at baseline significantly correlate with a poor prognosis in unresectable colorectal liver metastases (Connell et al, 2017). The increase in ALP level in GI cancer patients may probably due to destruction of tissues facilitating the leakage of enzyme and their appearance in blood circulation (Yadav, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…In our study, right colon (OR, 1.550; P = 0.012) and well and moderately differentiated tumours (OR, 2.203; P = 0.001) were independent predictive factors of KRAS mutations. STMs were reported to not be associated with KRAS mutations in several studies [21,27,28]. However, negative CA199 was found to be signi cantly correlated with KRAS mutations in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Of the 30 patients with KRAS mutation, a mutation was found in codon 12 (22), most had only one metastatic site (90.9%). The same did not occur with patients with mutations in codon 13 (8), of which half (50.0%) had only one metastatic site (p=0.029). Figure 2 illustrates the patient's overall survival by primary site and KRAS status.…”
Section: Study Design and Ethical Standardsmentioning
confidence: 78%